Agricultura urbana em Rio Claro (SP): produção e políticas públicas - Leme, Marina Koketsu (2012)
The importance of Urban Agriculture (UA) has been increasingly recognized in recent years. It emerges as an important survival strategy, especially for the poorest population who can consume and sell the food produced. It also has other advantages such as occupation of empty spaces, maintenance of green areas and the producers' increase of their self-esteem. But the practice also has certain barriers that require care, as the misuse of pesticides, the possibility of food contamination by water or land, theft of crops and other risks. The municipality of Rio Claro (SP), the object of the present study, is an example of a city that has several types of UA initiatives, however there is still no specific legislation directed to the sector. Thus, we sought to conduct an analysis of these urban gardens in the city considering the optical output and public policies. The field research included observations and interviews, using semistructured questionnaire applied to farmers responsible for the gardens. From the analysis of the results it's noted that the gardens in Rio Claro are still few, occupying a small area. Despite the difficulties, the UA provided, in general, an improvement in the respondents' quality of life. Moreover, the practice of UA has great potential for expansion and could be better exploited in the city. Thus some actions are required by the municipality to encourage urban agriculture in the city, extending its benefits and reducing its drawbacks.